Safety and Accuracy of Minimally Invasive Long Bone Fracture Repair Using a 2.5-mm Interlocking Nail: A Cadaveric Feline Study - Nabholz, Katrin; Pozzi, Antonio; Schmierer, Philipp A.; Smolders, Lucas A.; Knell, Sebastian C. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The Targon Vet System (TVS) is a 2.5-mm interlocking nail that can be applied minimally invasively. The purpose of this study was to test if the TVS could be safely applied percutaneously to different feline long bones without fluoroscopic guidance.Methods A gap fracture was created in 96 feline humeri, femora and tibiae (n = 32/group). Paired bones were randomly assigned to two treatment groups: (1) TVS inserted percutaneously with fluoroscopy and (2) TVS inserted percutaneously without fluoroscopy. Intraoperative evaluation (complications, procedure time, attempts), radiographs (pre-/postoperative alignment, length) and anatomical dissection (neurovascular injury, rotational alignment) were compared between treatment groups.Results The use of fluoroscopy did not lead to significant differences in any of the outcome measures. Intraoperative complications predominantly occurred in the distal humerus (12/32) and the proximal femur (7/32). In total, 20/96 complications occurred with no complications for the tibia. Neurovascular structures were only damaged at the medial side of the distal humerus (10/32).Clinical Significance We conclude that the TVS can be safely applied percutaneously to the tibia and with limitations to the femur in normal cadaveric cats without fluoroscopy. Despite the limitations of a cadaveric study, the high number of complications is leading us to consider the humerus not safe for the TVS. A learning curve has to be expected and technical recommendations should be respected to decrease complications.
Keywords: interlocking nail; minimally invasive fracture repair; fluoroscopy; safety and accuracy; cat